Education of Parents of Epilepsy Children - Dudarevič, Tatjana; Kuzborska, Zyta (Slauga. Mokslas ir praktika, 2021)
Epilepsy is a many-sided disease that manifests itself as seizures of various kinds and origin, which can start at any age, often in childhood. The nursing, training and treatment of a sick child have serious implications for the whole family. The most significant factor becomes the ability of a nurse to impart existing professional knowledge to a patient and his or her family and to teach about disease control measures. More informed patients and their families feel more in control of their illness than less informed patients and their relatives. People with epilepsy and the general public lack general information about the condition, knowledge about care and how to deliver it, and access to services. Educating loved ones is a key tool in disease control and prevention.The research was conducted in October and November of 2019 in one of the city hospitals in Vilnius. The analysis of questionnaire data before the training revealed that parents whose children suffer from epilepsy have lack of information about the disease. The questionnaire data after the training showed that parents acquired more knowledge and the results improved. The majority of parents whose children suffer from epilepsy is well informed about the disease. However, they have a lack of knowledge in relation to the factors provoking epileptic seizures. Besides, they are not aware when it is necessary to call the ambulance and when to use first aid medicines. The parents are interested in innovations related to epilepsy, treatment and care of a sick child. All the parents have a need to gain knowledge about the disease. The comparison of parents’ awareness of the disease before and after the training showed that parents had learnt to provide aid correctly during seizures. The training was effective.
Keywords: epilepsy; awareness; learning effectiveness